PENERAPAN PRINSIP-PRINSIP TATA KELOLA PEMERINTAHAN YANG BAIK (GOOD GOVERNANCE) PADA PELAYANAN PUBLIK DI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA LHOKSEUMAWE - Muhammad Adam Ramadhan; Yusrizal Yusrizal; Muhammad Nasir (Program Studi Magister Hukum Universitas Malikussaleh, 2025)
The satisfaction of the people of the city of Lhokseumawe with the system of government and also the services provided by the district of the town is not maximum. There are still some communities that feel unsatisfied with the services provided. The aim of this research is to analyze the application of the principles of good governance, obstacles, and efforts made to the public service in the offices of the Lhokseumawe Civil Records and Population Service. The research method uses qualitative methods with an empirical jurisprudence approach, using data from primary, secondary, and tertiary legal materials. Data collection techniques include interviews and documentation, as well as data analysis descriptively. Based on the results of the research, the application of the principles of good governance to the public service in the offices of the Lhokseumawe Civil Registration and Population Service has gone well. But there are still some problems. The obstacles faced are related to human resources, budget, understanding, and public awareness. The efforts are being made to improve the training programs, conduct e-KTP recordings for candidate beginner voters by going directly to schools, cooperate with private authorities and the central government, propose the addition of mobile e-KTP recording units that can reach hard-to-reach areas, educate about digital data security, and ensure that the IKD system used has met strict security standards.